1996
DOI: 10.1074/jbc.271.45.28259
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotides Demonstrate a Dominant Role of c-Ki-RAS Proteins in Regulating the Proliferation of Diploid Human Fibroblasts

Abstract: Although members of the RAS protein family (Ha-, Ki-, and N-RAS) are known to play a key role in normal cell proliferation and to be frequently mutated in naturally occurring tumors, it remains unclear which of these proteins functions to regulate growth in normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…There are three members of Ras proteins, i.e., H-Ras, K-Ras and N-Ras, and experiments with antisense and knockout studies showed that only K-Ras is required for normal cell growth and/or mouse development (30,31). In human cancer, 85% of these mutations involve K-Ras whereas less than 15% are from HRas (27).…”
Section: Ras Oncogene and The Erk/jnk Mapk Pathwaysmentioning
confidence: 99%
“…There are three members of Ras proteins, i.e., H-Ras, K-Ras and N-Ras, and experiments with antisense and knockout studies showed that only K-Ras is required for normal cell growth and/or mouse development (30,31). In human cancer, 85% of these mutations involve K-Ras whereas less than 15% are from HRas (27).…”
Section: Ras Oncogene and The Erk/jnk Mapk Pathwaysmentioning
confidence: 99%
“…Antisense Oligonucleotide Treatment-Treatment of Ki-ras transfectants was essentially as described (34). Cells were seeded at 2 ϫ 10 5 /well in six-well plates.…”
Section: Materials-mentioning
confidence: 99%
“…Cells were seeded at 2 ϫ 10 5 /well in six-well plates. 48 h later, the cells were washed with prewarmed serum-free insulin transferrin/selenious acid-supplemented DMEM and then incubated in this medium with a fixed ratio of oligonucleotide to Lipofectin (2.4 l of Lipofectin/100 M oligonucleotide) for 4 h. The oligonucleotide-containing medium was then replaced with normal growth medium, and growth was continued for 48 h to allow Ras turnover plus reduced Ras mRNA levels to result in reduced Ras protein levels (34).…”
Section: Materials-mentioning
confidence: 99%
“…Mutated K-ras is one of the most frequent genetic events in human cancer, with the highest incidences in pancreatic carcinomas (90%) and colorectal tumors (50%) (3,4). Various strategies have been attempted to selectively inhibit oncogenic Ras activity, including application of farnesyltransferase inhibitors (5,6), antisense technology (7)(8)(9), and small interference RNA (10). Although certain progress has been made in experimental models, therapeutic strategies to selectively inhibit activated ras oncogenes in human cancer remain to be established.…”
mentioning
confidence: 99%